2004
DOI: 10.1073/pnas.0400372101
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-unwinding mechanism of the ring helicase of bacteriophage T7

Abstract: Helicases are motor proteins that use the chemical energy of NTP hydrolysis to drive mechanical processes such as translocation and nucleic acid strand separation. Bacteriophage T7 helicase functions as a hexameric ring to drive the replication complex by separating the DNA strands during genome replication. Our studies show that T7 helicase unwinds DNA with a low processivity, and the results indicate that the low processivity is due to ring opening and helicase dissociating from the DNA during unwinding. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
98
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 47 publications
7
98
0
Order By: Relevance
“…On the other hand, an ensemble study of the ring-shaped helicase (E. coli DnaB) indicated an almost 7-fold difference in the unwinding rate depending on the sequence of the dsDNA substrate (39). Similarly, ensemble studies have shown that the non-ring-shaped UvrD helicase and ring-shaped T7 helicase, respectively, move 3-9-fold faster on ssDNA relative to their rates of dsDNA unwinding (29,40,41). 4 The latter observations imply that the unwinding rates of these helicases might depend on base pair stability.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, an ensemble study of the ring-shaped helicase (E. coli DnaB) indicated an almost 7-fold difference in the unwinding rate depending on the sequence of the dsDNA substrate (39). Similarly, ensemble studies have shown that the non-ring-shaped UvrD helicase and ring-shaped T7 helicase, respectively, move 3-9-fold faster on ssDNA relative to their rates of dsDNA unwinding (29,40,41). 4 The latter observations imply that the unwinding rates of these helicases might depend on base pair stability.…”
mentioning
confidence: 95%
“…The length of the dsNA region of the substrates was chosen carefully; it cannot be too short, because at room temperature 8 -16 bp of dsNA of a particular sequence can have ⌬G close to zero and can get spontaneously unwound (29,42). The length of the dsNA region cannot be too long, otherwise the unwound strands may reanneal behind the helicase during the reaction (29).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the biochemical and structural studies have shown that some helicases assemble into stable cooperative hexameric rings (3). These helicases include the Escherichia coli DnaB (6, 7) and Rho (8, 9), bacteriophage T4 gp41 (10, 11), and T7 gp4 (12)(13)(14). DNA passes through such a central channel and is unwound with a high processivity.…”
mentioning
confidence: 99%